Optimal location and size of logistics parks in a regional logistics network with economies of scale and CO2 emission taxes - Zhang, Dezhi; Eglese, Richard; Li, Shuangyan (Transport, 2018)
This paper proposes a model to address the design problem of a regional logistics network. In the proposed model, the decision variables include the location and size of logistics parks. The interaction between the logistics authority and logistics users as well as the effects of economies of scale and CO2 emission taxes on the logistics network design are explicitly considered. The proposed model is formulated as a bi-level formulation, in which the upper level aims to maximize total social welfare of the system by determining the optimal location and size of logistics parks with CO2 emission taxes consideration, whereas the lower level describes the logistics users’ choices for service routes. A heuristic solution algorithm is presented to solve the proposed model, and a numerical example is given to illustrate the applications of the proposed model and solution algorithm. The findings show that the optimal location and size of logistics parks depend on the realized logistics demand and the level of the economies of scale. The CO2 emission taxation can help to improve the total social welfare of the system and drive the logistics users to choose greener transportation modes.First published online 28 January 2015